Democracy and constitutionalism in the European Union : collected essays - Mancini, Federico, 1927-1999 (Hart Pub., 2000)
This collection of essays brings together the late Federico Mancini's most important writings in English, which concentrate largely on the issues of democracy, constitutionalism and individual rights in the European Union. The book presents the unique perspective of someone who witnessed the birth of European integration, was first an Advocate General and then a Judge of the Court of Justice of the European Community and who carried an unfaltering belief in the promises and advantages of a federal Europe.